Analysis of “Capillary and Venous Blood Glucose Accuracy in Blood Glucose Meters Versus Reference Standards: The Impact of Study Design on Accuracy Evaluations” - Thorpe, Gary H. (J Diabetes Sci Technol, 2018)
The article by Macleod and coauthors outlines an accuracy study of two blood glucose monitoring systems (BGMSs) against glucose-oxidase- and hexokinase-based assays showing how the reference/comparison method and inappropriate sample comparisons can affect accuracy conclusions. The dangers of independent institutions producing inappropriate conclusions when the methodology used for product regulatory or registration accuracy requirements is not according to best practice are stressed. The authors highlight several important aspects of a multistep accuracy evaluation protocol. However, it is essential that anyone undertaking or reporting BGMS accuracy studies should have a clear understanding of each and every protocol point, best practice, and how each can influence accuracy conclusions. Claims against regulatory accuracy criteria should be made only if the detailed specified protocol design and analysis is followed.